(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge and attitudes regarding contraception and sexually transmitted infections (STIs) among high school students at Tan Lap High School, Hanoi, Vietnam. Methods: A cross-sectional descriptive study was conducted among 391 students at Tan Lap High School, Hanoi, in 2023, using a structured self-administered questionnaire. Knowledge and attitudes were assessed using scoring scales and categorized based on a 70% cutoff. Results: A total of 85.9% of students had heard about contraception and STIs. However, only 7.2% correctly identified the fertile window in the menstrual cycle and 50.9% correctly recognized that pregnancy can occur after first sexual intercourse. The proportion of students with adequate knowledge was 47.6%. Regarding attitudes, 83.6% demonstrated positive attitudes. However, a considerable proportion still reported neutral responses on several key items. Conclusions: Students’ knowledge of contraception and STIs remains limited, while attitudes are generally positive. A gap persists between having heard of the topics and having accurate understanding and attitudes are not sufficiently well-defined in some areas. Therefore, strengthening sexual and reproductive health education is necessary, with a focus on fundamental reproductive knowledge, particularly the timing of the fertile window.